Moss stomata do not respond to light and CO2 concentration but facilitate carbon uptake by sporophytes: a gas exchange, stomatal aperture, and 13 C-labelling study - Kubásek, Jiří; Hájek, Tomáš; Duckett, Jeffrey; Pressel, Silvia; Šantrůček, Jiří (The New phytologist, 2021)
Stomata exert control on fluxes of CO2 and water (H2 O) in the majority of vascular plants and thus are pivotal for planetary fluxes of carbon and H2 O. However, in mosses, the significance and possible function of the sporophytic stomata are not well understood, hindering understanding of the ancestral function and evolution of these key structures of land plants. Infrared gas analysis and 13 CO2 labelling, with supporting data from gravimetry and optical and scanning electron microscopy, were used to measure CO2 assimilation and water exchange on young, green, ± fully expanded capsules of 11 moss species with a range of stomatal numbers, distributions, and aperture sizes. Moss sporophytes are effectively homoiohydric. In line with their open fixed apertures, moss stomata, contrary to those in tracheophytes, do not respond to light and CO2 concentration. Whereas the sporophyte cuticle is highly impermeable to gases, stomata are the predominant sites of 13 CO2 entry and H2 O loss in moss sporophytes, and CO2 assimilation is closely linked to total stomatal surface areas. Higher photosynthetic autonomy of moss sporophytes, consequent on the presence of numerous stomata, may have been the key to our understanding of evolution of large, gametophyte-independent sporophytes at the onset of plant terrestrialization.
Keywords: Plant Stomata; Bryophyta; evo-devo; photosynthesis; průduchy rostlin; zárodečné buňky rostlin; gas exchange; Germ Cells, Plant; environment; plant evolution; Carbon; uhlík; abscisic acid (ABA); stomata; oxid uhličitý; terrestrialization; Carbon Dioxide